Prevalence and associated factors of syphilis among female sex workers in East Africa: a systematic review and meta-analysis - Solomon Gedfie; Woldeteklehymanot Kassahun; Abdu Jemal; Muluken Gashaw; Alembante Bazezew; Marye Nigatie; Getinet Kumie; Tadesse Misganaw; Zewdu Tefera; Bewuketu Belete Alemu; Bahriew Mezgebu; Brhanu Kassanew; et al. (Frontiers in Public Health)
BackgroundSyphilis is the most common sexually transmitted infection caused by Treponema pallidum, a pathogen that is exclusive to humans. Syphilis is a highly treatable infection, but if left untreated, it can result in serious health complications, including adverse reproductive outcomes, diminished quality of life, and an increased risk of Human Immunodeficiency Virus (HIV) transmission. Female sex workers (FSWs) are considered a high-risk group for the transmission of syphilis. Therefore, this review aimed to estimate the pooled prevalence of syphilis and identify the associated factors among female sex workers in the East African region.MethodsThis systematic review and meta-analysis was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Databases such as PubMed/MEDLINE, Scopus, ScienceDirect, and Google Scholar search engines were explored to access eligible articles. STATA 11 statistical software was used to carry out the meta-analysis. A random-effects model was employed to estimate the pooled prevalence of syphilis and its predictors among female sex workers in the East African region. Higgen’s I2 test statistics was done to assess the heterogeneity of the included articles. Publication bias was evaluated visually using funnel plots and statistically through Egger’s weighted regression test.ResultsA total of 16,456 articles were retrieved, among which 24 studies involving 25,979 female sex workers were included in the final meta-analysis. The pooled estimates of syphilis among female sex workers were 14.7% (95%CI: 11.06–18.35) and I2 of 99.1%, p = 0.000. Sub-group analyses were conducted based on country and publication year to address heterogeneity. The results revealed that the highest prevalence was 18.48% (95% CI: 11.064–25.899) in Ethiopia and 2.79% (95% CI: 1.49–4.09) in Kenya. Regarding publication year, the prevalence was 16.3% (95% CI: 12.01–20.61) in studies conducted before 2014 and 12.5% (95% CI: 5.85–19.16) in studies conducted after 2014. Among the factors old age was a significant predictor of syphilis among female sex workers.ConclusionThis review revealed a relatively higher prevalence of syphilis compared to the global estimate. To effectively curb syphilis among female sex workers in East Africa, intervention strategies should address the high prevalence and key associated factors through comprehensive approaches.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024587246, CRD42024587246.